Pediatric Critical Care and the Climate Emergency: Our Responsibilities and a Call for Change - Wooldridge, Gavin; Murthy, Srinivas (Frontiers in Pediatrics, 2020)
Critical care is perhaps one of the most ‘climate-intensive’ divisions of health care. As greenhouse gas emissions continue to rise, the unprecedented threat of climate change has belatedly prompted an increased awareness of critical care’s environmental impact. Within our role as pediatric critical care providers, we have a dual responsibility to not only care for children at their most vulnerable, but also to advocate on their behalf. There are clear, demonstrable effects of our worsening climate on the health of children, with the resultant increased burden of pediatric critical illness and disruption to health care systems. From increasing wildfires and their effect on lung health, to the spread of vector-borne diseases such as dengue, and the increased migration of children due to a changing climate, – the effects of a changing climate are here, and we are beginning to see the changing epidemiology of pediatric critical illness. Ensuring that the effects of ongoing changes are minimized, including its future effects on child health, requires a multi-faceted approach. As part of this review we will use the Lancet Countdown on Climate Change indicators to explore the impact of paediatric critical care on climate change and the inevitable influence climate change will have on the future practice of paediatric critical care globally.